Karakteristik Sifat Amilografi Tepung Kentang (Solanum tuberosum L.) Varietas Atlantik Dan Hasil Modifikasi Heat Moisture Treatment Yang Ditanam Di Dataran Medium - Ajijah, Melia Siti; Utama, Raden Duhita Diantiparamudita (Jurnal Teknologi Pangan dan Hasil Pertanian, 2024)
Potatoes grow optimally in highlands areas at an altitude of more than 1000 meters above sea level (masl) with an ideal temperature of 18°C. However, continuously for potato cultivation in highlands can have negative impacts such as deforestation, erosion, landslides and floods. Therefore, the development of medium plain potatoes (300-700 masl) is increasing. This research aims to identify the amylographic characteristics of Atlantic potato flour from the high plain and atlantic potato flour from medium plain and the effect of modified by Heat Moisture Treatment . This study used an experimental method with t-test analysis. The results showed significant differences between the flour from highlands and medium plains with parameters of amylose content, amylopectin content and gel strength levels. Based on the gel strength value, highland potato flour is more stable than medium plain flour. In HMT modified flour and natural flour from medium plains and highlands there are significant differences in amylose content,  amylopectin content and whiteness. Based on the gel strength value, HMT modified flour shows better stability compared to natural flour from medium plains.